Mark for everyone - Wright, N.T. 1948- (SPCK, 2001)
Making use of his true scholar's understanding, yet writing in an approachable and anecdotal style, Tom Wright manages to unravel the great complexity of this extraordinary gospel. He describes it as 'one of the great books in the literature of the world; and part of its greatness is the way it reveals its secrets not just to high-flown learning, but to those who come to it with humility and hope'. Wright's stimulating comments are combined with his own translation of the Bible text.